COVID-19, macroeconomic performance and monetary policy efficiency of Latin American countries under Inflation Targeting: 2017-2022 - Vasconcelos, Marcos Roberto; Pereira dos Santos, Mayson Miranda (Sociedad y Economía, 2025)
The COVID-19 pandemic introduced a significant adverse supply shock, leading to severe recessions and accelerated inflation across global economies. This study investigates the impact of the pandemic on the macroeconomic performance and monetary policy efficiency of Latin American countries operating under Inflation Targeting (IT). Utilizing the output-inflation variability efficiency frontier method, we decompose changes in macroeconomic performance into those driven by supply shock variability and those attributable to monetary policy efficiency. Our analysis of ten Latin American countries reveals a universal decline in macroeconomic performance during the pandemic. Notably, only the central banks of the Dominican Republic and Mexico demonstrated a partial mitigation of the adverse supply shock, underscoring the importance of efficient monetary policy in crisis management. These findings highlight the critical role of effective monetary policies in stabilizing economies during periods of heightened uncertainty.